PERAN HUKUM DALAM MENJAMIN KEAMANAN REKENING NASABAH (STUDI ATAS KEBIJAKAN PERBANKAN DI Indonesia) - balubun, christina orvala aurel; Djajaputera, Gunawan (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2025)
This research aims to analyze the extent of the role of law in ensuring the security of customer accounts, as well as to explore the effectiveness of banking policies implemented by the relevant authorities. This research applies a sociological juridical approach, using a case study design and descriptive-qualitative analysis. The research results reveal that Indonesia has a strong legal basis regarding banking, as contained in the provisions of Law no. 10 of 1998, which regulates banks' obligations to maintain bank secrets and protect customer data from protection. Apart from that, legal protection for customers is also regulated in Law Number 8 of 1999 concerning Consumer Protection, which gives customers the right to obtain clear, correct and not excessive information regarding banking products or services. However, its implementation cannot be separated from various challenges, including the rise of cybercrime which is increasingly sophisticated and organized, oddities because not all banks have equivalent security systems in dealing with digital threats, as well as obstacles to the effectiveness of these policies which occur due to inconsistencies between existing regulations, and implementation in the field. Therefore, more intensive education and counseling regarding the importance of personal data security remains a very urgent matter that must be carried out on an ongoing basis.